2020
DOI: 10.1039/d0fo01116a
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B prevents body weight gain and regulates gut microbiota and LPS/TLR4 signaling pathway in high-fat diet-induced obese mice

Abstract: Salvianolic acid B (Sal B) exhibits an anti-obesity activity, yet the underlying mechanism linking this effect to metabolic endotoxemia remains unexploited. For this purpose, high-fat diet-induced obese mice were orally...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 50 publications
3
25
0
Order By: Relevance
“…F16 was also identified as novel superior microbiota in probiotics intervention groups, which was consistent with a previous study (39). Based on LEfSe analysis, the genera Oscillospira, Lactococcus, and Mucispirillum, which were the characteristic flora of the HFD group, were found to be positively correlated to the LPS, suggesting that these bacteria may play a pro-inflammatory role in the development of obesity and IR (37,40). It was also speculated whether the disorder of glycolipid metabolism could be modified by the beneficial gut microbes by preventing inflammation.…”
Section: Discussionsupporting
confidence: 88%
“…F16 was also identified as novel superior microbiota in probiotics intervention groups, which was consistent with a previous study (39). Based on LEfSe analysis, the genera Oscillospira, Lactococcus, and Mucispirillum, which were the characteristic flora of the HFD group, were found to be positively correlated to the LPS, suggesting that these bacteria may play a pro-inflammatory role in the development of obesity and IR (37,40). It was also speculated whether the disorder of glycolipid metabolism could be modified by the beneficial gut microbes by preventing inflammation.…”
Section: Discussionsupporting
confidence: 88%
“…LPS, the main component of outer membrane of Gram-negative bacteria, is believed to be enriched by gut microbiota [ 52 ]. Serum LPS content can reflect the change of intestinal permeability, and then reflect the level of gut microbiota disorders [ 53 ]. HFD feeding can promote the proliferation of endotoxin-producing bacteria [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that salvianolic acid A in Salvia miltiorrhiza can inhibit the oxidation of LDL, inhibit inflammation, and improve endothelial function to ameliorate AS [ 135 , 136 ]. Salvianolic acid B (Sal B) can reverse gram-negative bacteria in HFD mice, which is positively associated with LPS elevation and increases the abundance of adlercreutzia to improve gut permeability [ 116 ]. By maintaining intestinal motility, Salvia miltiorrhiza could improve the tolerance of intestinal mucosal epithelial cells to ischaemia and hypoxia to protect intestinal barrier function [ 117 ].…”
Section: Therapeutic Intervention With Tcmmentioning
confidence: 99%
“…Thus, Salvia miltiorrhiza can reduce metabolic endotoxaemia by reducing LPS and protecting the intestinal barrier. Furthermore, in Lin's study [ 116 ], salvianolic acid B inhibited the LPS/TLR4 signalling pathway by inhibiting the abundance of gram-negative bacteria and improving insulin sensitivity and lipid metabolism disorder in HFD mice.…”
Section: Therapeutic Intervention With Tcmmentioning
confidence: 99%